Sistem Monitoring Kesehatan Karyawan Menggunakan Wemos D1 Untuk Antisipasi Penularan Covid 19 Berbasis Internet Of Things - Nuris Dwi Setiawan; Irene Ongkowijoyo (Teknik Komputer Politeknik Negeri Sriwijaya, 2021)
The Covid-19 pandemic has had a negative impact on the economic sector, many companies have laid off employees to reduce transmission, but this has caused a bigger problem. The decline in production levels threatens to make companies lose money, this is responded well by the government by issuing a